SYNTHESIS OF AMIDE DERIVATIVES BASED ON GLYCYRETHIC ACID BY EDCI/HOBT ACTIVATION WITH 3-AMINOPROPYL IMIDAZOL - Turlibekov , Diyorbek; Yuldashev , Xabibulla (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
in this work, new amide derivatives were synthesized with 3-aminopropyl imidazole (3-API) by activating the carboxyl group of glycyrrhizic acid (GlC) in the presence of EDCI (1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride) and HOBt (1-hydroxybenzotriazole). The reaction was carried out in an inert gas medium, and the synthesis was carried out with a high chemical total (95%). [1] The resulting compound was confirmed using IR and mass spectrometry. The formation of the amide bond was determined by the absorption bands 1642 (C=O) and 3354 cm-1 (N-H). The results show that the EDCI/HOBt system is an effective reagent combination for amide synthesis based on natural triterpenoids.